Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve the equation. Express your answer in exact simplest form:

[tex]\[\sqrt[3]{4x - 1} - 4 = 2\][/tex]

The solution set is [tex]\(\square\)[/tex].


Sagot :

Certainly! Let's solve the equation step-by-step.

We are given the equation:

[tex]\[ \sqrt[3]{4x - 1} - 4 = 2 \][/tex]

Step 1: Isolate the cube root term.

First, add 4 to both sides of the equation to isolate the cube root term:

[tex]\[ \sqrt[3]{4x - 1} = 2 + 4 \][/tex]

[tex]\[ \sqrt[3]{4x - 1} = 6 \][/tex]

Step 2: Remove the cube root by cubing both sides.

To eliminate the cube root, cube both sides of the equation:

[tex]\[ \left(\sqrt[3]{4x - 1}\right)^3 = 6^3 \][/tex]

[tex]\[ 4x - 1 = 216 \][/tex]

Step 3: Solve for [tex]\( x \)[/tex].

Next, add 1 to both sides to solve for [tex]\( 4x \)[/tex]:

[tex]\[ 4x = 217 \][/tex]

Now, divide by 4:

[tex]\[ x = \frac{217}{4} \][/tex]

[tex]\[ x = 54.25 \][/tex]

So, the solution set is:

[tex]\[ \boxed{54.25} \][/tex]